Integrating infant mental health practice models in nursing. Issue 1 (8th January 2020) - Gordon, Jessica M.; Gaffney, Kathy; Slavitt, Hannah C.; Williams, Amy; Lauerer, Joy A.
Abstract: Problem: During the first years of life, the brain is developing rapidly and is especially vulnerable to the effects of trauma and or stress. Early exposure to such early trauma or stress predisposes young children to mental health problems. The practice of infant mental health (IMH) focuses on preventing negative mental health outcomes in infancy and toddlerhood. Currently, IMH is not standard practice in nursing. To enhance IMH in nursing, this manuscript provides an overview of IMH practice models, discusses nursing implications of each model and presents a model for integrating IMH into nursing practice. Methods: A scoping review was conducted with a literature search utilizing the keywords "infant mental health" AND "models of care" in the PubMed and CINHAL databases from 2002 to 2018. Findings: Twenty of the publications retrieved met search criteria. Among the 20 articles, 10 addressed clinical‐based content related to IMH practice and 10 addressed nonclinical‐based content associated with IMH educational training, policy development, or system‐based models of care. Conclusions: Nurses are well positioned to impact IMH. The model presented provides the nursing process as a practical framework for the integration of IMH in nursing practice that can be expanded upon as IMH evolves.